The prevalence and severity of health problems in youth elite sports: A 6-month prospective cohort study of 320 athletes - Moseid, C. H.; Myklebust, G.; Fagerland, M. W.; Clarsen, B.; Bahr, R. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Little is known regarding the overall health of youth elite athletes. Our aim was to describe the prevalence and severity of health problems in a cohort of youth elite athletes representing a variety of endurance, team, and technical sports. Elite sport athletes (N = 260, 16.2 years) from different Sport Academy High Schools in Norway, and a group of their teammates (N = 60, 16.4 years) attending regular high schools, were included in the study. The Oslo Sports Trauma Research Centre (OSTRC) questionnaire on health problems was used to self-report injuries and illnesses for 26 weeks. At any given time, an average of 43% [95% CI: 37%-49%] of the elite sport athletes had some form of health problem and 25% [20%-31%] had substantial health problems. The prevalence of health problems was similar between the elite team sport athletes and their teammates, except for substantial injuries (22% [16%-30%] vs 10% [5%-20%]). Endurance sport athletes reported more illnesses (23% [15%-35%]) than technical and team sport athletes (10% [5%-20%] and 8% [4%-14%]). In contrast, technical and team sport athletes reported more injuries (36% [95% CI: 25-48] and 37% [95% CI 29-45]) compared to endurance sport athletes (15% [8%-25%]). The total impact of health problems was roughly split in thirds between overuse injuries (37%), acute injuries (34%), and illnesses (30%). This is the first prospective study to present self-reported injury and illness data in a large heterogeneous group of youth elite athletes, documenting a subst